Tinjauan Ketepatan Kode Penyakit Tuberkulosis Paru Berdasarkan ICD-10 pada Pasien Rawat Inap di RSKD Duren Sawit Tahun 2021 - Vania Rachma Putri; Puteri Fannya; Deasy Rosmala Dewi; Lily Widjaja (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Coding accuracy is the process of conforming to the diagnosis code that has been determined by the coding officer based on ICD-10 which greatly affects data reporting and administration. Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which causes disturbances in the respiratory tract. In RSKD Duren Sawit pulmonary tuberculosis is included in the 10 biggest diseases. The purpose of this study was to determine the accuracy of the pulmonary tuberculosis disease code based on ICD-10 in inpatients at RSKD Duren Sawit in 2021. This study used a descriptive method with a quantitative approach that took 80 samples using a saturated sample technique by means of observation and interviews. The results obtained from 80 samples of the accuracy of the pulmonary tuberculosis code of inpatients at RSKD Duren Sawit found that 56 (70%) and 24 (30%) were inaccurate. There are factors that affect the inaccuracy of using the 5M (Man, Money, Material, methode, Machine) element, namely the man element due to the inappropriateness of the coding officer's profession and lack of thoroughness and the element of the coding SOP method which is still being revised. Suggestions should be officers who do coding in accordance with their profession or medical recorders.